How Reliable are Farmers’ Perceptions about Climate Change? A Case Study in the Upper East Region of Ghana - Zakaria, Abdul-Razak; Matsui, Kenichi (International Journal of Environment, Agriculture and Biotechnology, 2020)
The 2014 IPCC report reiterated the importance of local farmers’ perceptions about climate change. A growing number of scientists supports that farmers’ in-depth understanding of climate change hazards and their active participation in mitigation actions are key to improving adaptation. This paper attempts to analyze smallholder rice farmers’ perceptions and knowledge about climate change hazards in the Upper East Region of Ghana mainly by looking at national climatic data and the results of the questionnaire survey we conducted. The climatic data were further analyzed through the Mann-Kendall trend test to find any relations between actual rainfall and temperature changes with farmers’ observations. Our analysis on perceptions shows that more than 60% of the respondents experienced climate hazards in the forms of increasing temperature, decreasing rainfall and changing planting time. These results are also supported by the Mann-Kendall trend test. The change in planting time is attributable to the increasing coefficient of variation of the annual rainfall from 16.5% (1996 – 2005) to 28.1% (2006 – 2015). It is also due to substantial rainfall deviations within the Region in May, from 1,000 mm in the decade between 1996 and 2005 to 500 mm in the following decade (2006 – 2015). We argue that farmers’ observations are largely reliable particularly in observing changes in rainfall patterns. Their observations can also supplement insufficient local meteorological records to better understand local climate change conditions in Western Africa.